Advancements in two-dimensional nanomaterials for regenerative medicine in skeletal muscle repair - Hongyu Bai; Lu Liu; Zhiwen Luo; Renwen Wan; Jiwu Chen (Materials Today Bio)
Skeletal muscle, the largest organ in the human body, plays vital roles in movement, heat generation, and internal organ protection. While healthy muscle can regenerate effectively, its regenerative capacity declines in conditions like congenital muscular dystrophy, severe trauma, or aging. Two-dimensional (2D) nanomaterials, with unique physicochemical properties such as high surface area, excellent biocompatibility, and tunable mechanical and electrical properties, have shown great promise in different forms of muscle injury, particularly in volumetric muscle loss (VML). Recent studies highlight their diverse applications in muscle regeneration, acting as cell recruitment platforms, drug delivery carriers, structural scaffolds, and anti-inflammatory agents. Additionally, their biological effects and intelligent responsiveness are emerging as key features. Despite these advances, safety concerns regarding toxicity and biodegradability remain a challenge for clinical application. To unlock the full potential of 2D materials, further research is needed, especially through interdisciplinary collaboration to better understand their biological effects. By addressing safety issues and harnessing their multifunctional and intelligent characteristics, 2D nanomaterials can offer a more effective and sustainable approach to skeletal muscle repair, paving the way for next-generation therapies in regenerative medicine.